2018
DOI: 10.1016/j.steroids.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin actions in the nucleus

Abstract: Paxillin is a group III LIM domain protein that is best characterized as a cytoplasmic scaffold/adaptor protein that functions primarily as a mediator of focal adhesion. However, emerging studies indicate that paxillin's functions are far broader. Not only does paxillin appear to regulate cytoplasmic kinase signaling, but it also cycles between the cytoplasm and nucleus, and may serve as an important regulator of mRNA trafficking and subsequent translation. Herein, we provide some insights suggesting that paxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…It contains four cysteine-histidine-enriched LIM domains that form zinc fingers, suggesting that PXN could bind DNA and act as a transcription factor. Consistently, PXN is reported to locate to the nucleus which is regulated by phosphorylation (Dong et al, 2009;Ma and Hammes, 2018). In LUAD, expression of PXN is correlated with tumor progression and metastasis (Song et al, 2010;Mackinnon et al, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…It contains four cysteine-histidine-enriched LIM domains that form zinc fingers, suggesting that PXN could bind DNA and act as a transcription factor. Consistently, PXN is reported to locate to the nucleus which is regulated by phosphorylation (Dong et al, 2009;Ma and Hammes, 2018). In LUAD, expression of PXN is correlated with tumor progression and metastasis (Song et al, 2010;Mackinnon et al, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…For NSCs cultured on PDA-CF for 3 days, immunohistochemistry showed increased expression of vinculin protein ( Figure 7A ), and quantification of vinculin ( Figure 7B ) showed increased expression compared to the CF group, which suggests that PDA might promote NSC proliferation by regulating the expression of vinculin. The interaction between integrins and the ECM induces the expression of paxillin, which is a central component of focal adhesion complexes and plays a vital role in cell attachment, spreading, and migration through the transduction of extracellular signals into intracellular responses (Lo'pez-Colome et al, 2017 ; Ma and Hammes, 2018 ). Cells attach to the ECM through trans-membrane integrin proteins and use these interactions to sense their environment (Kechagia et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence this will affect proper JNK activation and AP-1 transcription factor activation thereby providing a positive feedback for EGFR expression [62] . Alternatively, paxillin may affect the expression of EGFR by its known role in the regulation of gene expression through its interaction with ERK [63,64] , poly-A-binding protein [65] , Abl [66,67] and steroid receptors, or through its own ability to undergo nucleocytoplasmic shuttling [37,38,[68][69][70][71] .…”
Section: Discussionmentioning
confidence: 99%
“…Paxillin is a 68 kD multidomain adaptor protein associated with focal adhesions [26][27][28][29][30][31] . It is long known to function as a scaffold to integrate multiple signaling pathways involved in matrix adhesion dynamics and cell migration [27,[31][32][33][34][35][36] , and recently, it was shown to play a role in the nucleus in relation to mRNA transcription and subsequent translation [37,38] . Few studies have identified paxillin as a JNK substrate [8,24,25] .…”
Section: Introductionmentioning
confidence: 99%